Antimicrobial activity of Bothrops asper and Porthidium nasutum venom on purple passion fruit (Passiflora edulis f. edulis) phytopathogens (2023)
ABSTRACT: The most important pathogens causing high damage to fruit and vegetable crops are bacteria and fungi; among them Xanthomonas and Fusarium respectively are in the phytopathogens responsible of diseases in those crops. In Colombia, the crop of Passiflora edulis f. edulis occupies a position preferential within international market. However different pathologies affect their production, one of them is the infectious diseases and are caused by microorganisms as Xanthomonas and Fusarium. The control includes application of pesticides or antibiotics, but to some of them the microorganisms have develop resistance is widespread, and others are restricted associated to the impact on the environment and effects in animal and human healthy. Then find other alternatives is necessary, in this work the snake venoms of the vipers Bothrops asper and Porthidium nasutum were evaluated in ability to inhibit growth of these microorganism isolated of purple passion fruit crops with typical symptoms of diseases associated with infections by microorganisms. For these antimicrobial assays were performed in agar culture and broth microdilution. The results showed growth inhibition of 80% to B. asper against Xanthomonas axonopodis and 70% Xanthomonas perforans. The minimum inhibitory concentration was 31,2 µg mL-1 to B. asper and 500 µg mL-1 to P. nasutum to both bacteria. Nevertheless, the activity against F. oxysporum was low. The isolation of compounds responsible of this activity will contribute to the development of new molecules for antimicrobial agents against phytopathogens affecting purple passion fruit crops.